Interrelationship between the clearance in the “Bushing-plunger block” combination and working fluid leaks - Viunyk, Olha; В'юник, Ольга Володимирівна; Lysenko, D. (Запоріжжя: ТДАТУ, 2025)
The work is part of a series of articles devoted to increasing the durability of plunger pairs of axial piston pumps. Studies conducted earlier have shown that the parameters of the technical condition that cause volume losses and affect the operability of the hydraulic drive of the transmission drive include wear of the connection “block sleeve - plunger”. In this case, we will be interested in the volume of working fluid leaks caused by wear of the connection parts.
Keywords: Bushing-plunger block